PROFESSIONAL REQUIREMENTS AND COMPETENCIES IN VR-BASED EDUCATIONAL PROCESSES AT TOP TECHNICAL HIGHER EDUCATION INSTITUTIONS (PROBLEMS AND SOLUTIONS OF SCIENTIFIC AND INNOVATIVE RESEARCH, 2024)
Virtual reality (VR) is transforming education, particularly in technical higher education institutions, by enabling immersive learning environments. This paper examines the professional requirements and competencies necessary for integrating VR-based educational processes in top technical universities. The study highlights the required skill sets for educators, the infrastructure demands, and the competencies students must develop. Using reliable references, we provide a structured analysis supported by tables and discuss the implications for policy and curriculum design.